Enhancing service quality implemented by food and beverage at The Saujana, Kuala Lumpur / Azreen Farahida Bt. Abd.Hamid - Abd. Hamid, Azreen Farahida (Faculty of Business Management, 2006)
Service quality is a growing concern for many service firms in Malaysia. Today service firms are paying more attention than ever to the needs and expectations of the customers by consistently improving the quality of service provided to their customers. Hotel industry is one of the services that contributed to the growth of economic in Malaysia. In a hotel group, service quality is very important due to the high level of customer contact. In 1990, Malaysia has launched "Visit Malaysia Year" campaign and the tourism industry had become the third largest source of income for foreign exchange. This was due to the development of new tourism products as well as improved promotion and marketing efforts. This study was focus towards the goal of enhancing the service quality implemented by Food and Beverage Outlets at The Saujana, Kuala Lumpur. The objectives of this research is to find out the level of customer's satisfaction towards service quality in terms of tangible, reliability, responsiveness, assurance and empathy that provided by The Saujana. 100 questionnaires that have been modified from the SERVQUAL instruments were directly administered to the customers and it has contained 30 items, which have been divided into five dimensions of the SERVQUAL. All data collected was analyzed by using frequency analysis and cross tabulation. Result from the analysis stated that customers are satisfied with service quality provide by Food and Beverage Outlets at The Saujana. However, there so many aspects need to be focused in order to achieve high customer's satisfaction in terms of staffs attitude and responsiveness towards their jobs. Some recommendations were to improve the service performances.